2013
DOI: 10.7860/jcdr/2013/4416.2749
|View full text |Cite
|
Sign up to set email alerts
|

Popular Misconceptions Regarding the Diabetes Management: Where Should We Focus Our Attention?

Abstract: Background: Diabetes mellitus is a universal health problem with a global prevalence of 1.3%. India is known as the "Diabetes capital of the world" as it harbours the largest number of diabetes patients. There is lack of awareness about the existing interventions for preventing diabetes and for the management of the complications. One of the barriers in the way of seeking health care advice is the misconception about the disease, which revolves around all the aspects of diabetes, which include its prevention, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 12 publications
5
19
0
Order By: Relevance
“…Instrument. This study sought to assess patients' knowledge of diabetes using a questionnaire specifically developed for this study based on literature review, [7,8,10,[15][16][17][18][19][20][21][22][23][24] paper-and web-based patient education materials, and expert opinion. During questionnaire design, first, the questions collected from the above sources were divided into categories such as efficacy, side effects, medication use, complications, daily healthcare, and disease awareness.…”
Section: Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Instrument. This study sought to assess patients' knowledge of diabetes using a questionnaire specifically developed for this study based on literature review, [7,8,10,[15][16][17][18][19][20][21][22][23][24] paper-and web-based patient education materials, and expert opinion. During questionnaire design, first, the questions collected from the above sources were divided into categories such as efficacy, side effects, medication use, complications, daily healthcare, and disease awareness.…”
Section: Surveymentioning
confidence: 99%
“…Indeed, lack of awareness and insufficient understanding of diabetes could lead to adverse consequences. In recent years, a few studies have investigated patients' knowledge about their diabetes [7][8][9][10] or examined the association between diabetesrelated self-care knowledge and glycemic control [10][11][12][13]. For example, a study conducted by Mann et al demonstrated that certain misconceptions about diabetes and its treatment were associated with poor glycemic control [10].…”
Section: Introductionmentioning
confidence: 99%
“…Considering 50% prevalence of the awareness about diabetes with a 10% relative error, sample size came out to be 400. 6 400 known diabetic patients of study area who were above 18 years and had given their consent to participate in the study were included. Known diabetics were enrolled in the study because they practice various methods to control the disease and carry various beliefs about the disease.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the myths and misconceptions about diabetes mellitus, is important in providing excellent care and health education to both patients and healthy individuals. 6 Aim of study was to know the level of myths and misconceptions about diabetes and its treatment among urban diabetics of Haryana.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of diabetes is rapidly increasing worldwide, and the condition is projected to affect 300 million people by 2025, approximately one-third of whom will develop diabetic nephropathy (DN) [ 1 ]. DN is manifested by the accumulation of extracellular matrix proteins and an irreversible decline in renal function and is the leading cause of end-stage renal disease (ESRD) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%